2014
DOI: 10.1016/j.coph.2014.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Test driving ToxCast: endocrine profiling for 1858 chemicals included in phase II

Abstract: Identifying chemicals, beyond those already implicated, to test for potential endocrine disruption is a challenge and high throughput approaches have emerged as a potential tool for this type of screening. This review focused the Environmental Protection Agency’s (EPA) ToxCast™ high throughput in vitro screening (HTS) program. Utility for identifying compounds was assessed and reviewed by using it to run the recently expanded chemical library (from 309 compounds to 1858) through the ToxPi™ prioritization schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 13 publications
0
61
0
Order By: Relevance
“…The previous iteration of the signature was expanded to include newly available ToxCast assay data on critical vascular developmental targets including assays that measure events along the estrogen receptor (ER) pathway such as binding, dimerization, and transcription that could be relevant to downstream VEGF production, as well as assays that measure inhibition of proliferation in human primary vascular (endothelial and smooth muscle) cells. The ToxCast Phase I/II libraries (1060 unique compounds) were ranked according to their cumulative activity across 124 signature assays and visualized using the Toxicological Prioritization Index (ToxPi) tool [8; 18; 19]. This approach functions to rank chemicals based on their putative ability to disrupt blood vessel development.…”
Section: Methodsmentioning
confidence: 99%
“…The previous iteration of the signature was expanded to include newly available ToxCast assay data on critical vascular developmental targets including assays that measure events along the estrogen receptor (ER) pathway such as binding, dimerization, and transcription that could be relevant to downstream VEGF production, as well as assays that measure inhibition of proliferation in human primary vascular (endothelial and smooth muscle) cells. The ToxCast Phase I/II libraries (1060 unique compounds) were ranked according to their cumulative activity across 124 signature assays and visualized using the Toxicological Prioritization Index (ToxPi) tool [8; 18; 19]. This approach functions to rank chemicals based on their putative ability to disrupt blood vessel development.…”
Section: Methodsmentioning
confidence: 99%
“…Such prioritization efforts are being used by the Endocrine Disruption Screening Program (EDSP), where Phase I and II ToxCast data are evaluated to reduce the number of chemicals moving on to more traditional animal-based tests for disruption of the estrogen, androgen, and thyroid endocrine pathways. A similar approach has also been recommended for other pathways, including those related to the glucocorticoid and PPAR signaling networks (Filer et al , 2014b; Reif et al , 2010). To date, ToxCast prioritized chemical sets have yet to be screened in biologically relevant assays for evaluating human adipogenesis.…”
mentioning
confidence: 99%
“…Overall, effects of BPA alternatives have been poorly investigated. Recent studies have revealed that less studied endocrine-related systems such as glucocorticoid, PPAR, monoamine, noradrenaline and serotonin pathways could be targets of endocrine disruption (Filer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%